Tolerance in Creating Healthy Politics From an Islamic Perspective - Setiawan, Anton; Budiyanti, Nurti; Nufus, Jihaadun; Salsabila, Mutiara; Thariqsa, Resvi (Department of Civic Education, 2023)
In political practice in Islamic countries, disputes often occur between communities due to differences of opinion. The most appropriate solution to overcome this problem is to apply tolerance. Tolerance in politics will create healthy political relations for the prosperity of citizens. This research uses a qualitative descriptive approach to look at the condition of religious tolerance which recently is often directed at Islam, that Islam is an intolerance religion. This approach aims to prove the accusation that Muslims are the most tolerant group. The results of this study indicate that from an Islamic perspective it is emphasized that we as Muslims must have an attitude that upholds tolerance and maintains harmony so that divisions between religions will not occur. The data in this study includes primary data obtained from interviews with three speakers, namely practitioners, teachers, and students who have insight into tolerance in the political sphere from an Islamic perspective, as well as secondary data in the form of Hadith, Qur'anic postulates, and previous research journals. The results of the research conducted resulted in the conclusion that knowledge and understanding of inter-religious tolerance is important. People must explore knowledge about inter-religious tolerance to learn because we Muslims have to be political. The political strategy in Islam is by da'wah. Harmonization between religious communities is by creating a peaceful atmosphere to establish better communication and help each other if there are difficulties in order to create a harmonious atmosphere in the community. Therefore, in the Islamic perspective it is emphasized that we as Muslims must have an attitude that upholds tolerance and maintains harmony so that there will be no divisions between religious communities.